The effectiveness of health education package on knowledge, attitude and practice of influenza a (H1N1) among secondary school children in Kelantan - Jamil, Wan Arfah Nadiah Wan Abdul (2011)
Health education is crucial in providing individuals with the information, skills and motivation necessary for decision making about lifestyle and personal health behavior. An effective health education is vital as the pandemic will affect a very large numbers of people. People must be well informed with factual and up to date information. This study was conducted to determine level of knowledge, attitude and practice among secondary school children on influenza A (H1N1) and to evaluate the effectiveness of health education package on influenza A (H1N1). A community intervention trial was conducted among secondary school children in two districts in Kelantan; namely Kota Bharu and Bachok from July to December 2010. Students in one school in Bachok were allocated as the intervention group and those in Kota Bharu as the control group. Form four students were selected by using cluster sampling according to class. Data was collected using knowledge, attitude and practice questionnaire before, immediately after and intervention. The intervention group was given a lecture, video shows and printed materials (booklet and pamphlet) on influenza A (H1N1). The control group was given a video show on hazards of smoking. Repeated measures analysis of covariance (ANCOVA) was applied in data analysis. A total of 436 students in SMK one month after the Bachok (intervention group) and SMK. Kota (control group) were included in the study. The study involved all Malay students aged 16 years old. More than half of them were females (62.6% for control group and 52.8% for intervention group). The baseline mean (SD) for knowledge, attitude and practice scores were 69.35 (8.81), 65.77 (7.14) and 35.42 (6.19) respectively. After controlling the potential numerical covariate, there were significant improvements in knowledge (F=53.70, p<0.001) and attitude (F=5.37, p=0.005) scores in the intervention group compared to the control group over time. However there was no significant difference between the groups for practice. This study suggests that health education package is an essential component in improving knowledge and attitude of students on influenza A (H1N1). Having good knowledge and attitude will lead to better prevention and control and this in turn will reduce the incidence of disease and cost due to influenza A (H1N1) infection and may halt the epidemic.